Triplet entropy analysis of hemagglutinin and neuraminidase sequences measures influenza virus phylodynamics - Gerhardt, Günther J.L.; Takeda, Agnes A.S. [UNESP]; Andrighetti, Tahila [UNESP]; Sartor, Ivaine T.S.; Echeverrigaray, Sergio L.; de Avila e Silva, Scheila; dos Santos, Laurita; Rybarczyk-Filho, José L. [UNESP] (Elsevier, 2013)
The influenza virus has been a challenge to science due to its ability to withstand new environmental conditions. Taking into account the development of virus sequence databases, computational approaches can be helpful to understand virus behavior over time. Furthermore, they can suggest new directions to deal with influenza. This work presents triplet entropy analysis as a potential phylodynamic tool to quantify nucleotide organization of viral sequences. The application of this measure to segments of hemagglutinin (HA) and neuraminidase (NA) of H1N1 and H3N2 virus subtypes has shown some variability effects along timeline, inferring about virus evolution. Sequences were divided by year and compared for virus subtype (H1N1 and H3N2). The nonparametric Mann-Whitney test was used for comparison between groups. Results show that differentiation in entropy precedes differentiation in GC content for both groups. Considering the HA fragment, both triplet entropy as well as GC concentration show intersection in 2009, year of the recent pandemic. Some conclusions about possible flu evolutionary lines were drawn. © 2013 Elsevier B.V.
Keywords: Entropy; H1N1; Influenza; Sequence analysis; nucleotide; virus hemagglutinin; virus sialidase; DNA base composition; entropy; genetic organization; genetic variability; Influenza virus; Influenza virus A H1N1; Influenza virus A H3N2; molecular phylogeny; nonhuman; pandemic influenza; priority journal; sequence analysis; species comparison; strain difference; triplet entropy analysis; viral genetics; Orthomyxoviridae